Estudio preliminar del úrsido del yacimiento del Cuaternario medio de Pinilla del Valle (Madrid) - Alferez Delgado, F.; Molero, G. (Coloquios de Paleontología, 1985)
Among the paleontologie material lately excavated from the midíd Quaternary deposit of Pinilla del Valle (Madrid), we should remark a practically complete skull, belonging to a big bear. Denticion of this animal show some morphologic similarities witb the aretoid line even though its structure and morphology are enough different from those ¿f the extant Ursus aretos. Ihis skull is not easily comparable with dic species Ursus prearctos, because this species was erected by BOULE (1906) based upon a fragmcntary material composed maiiily of isolated teeth. Tbis species, as its name says, was considered as belonging to a archaic form of U. arcios. The discovery of this skull together with mandibular rcsts and isolated teeth allows us to argument dic similarity x.víth the aretoid line and the validity and/or actual status of species defined by BOULE.
Keywords: Mammalia; Ursidae; Ouaternaiy